PENGARUH ANALISIS GREEN PURCHASE INTENTION DENGAN GREEN TRUST SEBAGAI VARIABEL INTERVENING PADA GREEN PRODUCT PERAWATAN TUBUH - Wahyumar, Hatri (2022)
This study was directed to decide the impact of green perceived value, environmental concern, and green trust on green purchase intention. Furthermore, an investigation of green trust is additionally led as an intervening variable that intervenes the connection between green perceived value and environmental concern on green purchase intention. This exploration was directed on 130 respondents who are customers of green body care products in the Greater Jakarta area. Data collection is done on the web. Then the data is processed using SmartPLS 3.0. The outcomes showed that green perceived value affected green trust. In the meantime, environmental concern affects green trust. The outcomes likewise show that green trust meaningfully affects green purchase intention. Then, at that point, it was found that green trust only mediates the connection between green perceived value towards green purchase intention, while the connection between environmental concern towards green purchase intention cannot be mediated.